Genetic Labeling of Neuronal Subsets through Enhancer Trapping in Mice - Kelsch, Wolfgang; Stolfi, Alberto; Lois, Carlos (PLOS ONE, 2012)
The ability to label, visualize, and manipulate subsets of neurons is critical for elucidating the structure and function of individual cell types in the brain. Enhancer trapping has proved extremely useful for the genetic manipulation of selective cell types in Drosophila. We have developed an enhancer trap strategy in mammals by generating transgenic mice with lentiviral vectors carrying single-copy enhancer-detector probes encoding either the marker gene lacZ or Cre recombinase. This transgenic strategy allowed us to genetically identify a wide variety of neuronal subpopulations in distinct brain regions. Enhancer detection by lentiviral transgenesis could thus provide a complementary method for generating transgenic mouse libraries for the genetic labeling and manipulation of neuronal subsets.